Etyka mediosfery - Lepa, bp Adam (Annales. Etyka w Życiu Gospodarczym, 2010)
The paper presents the structure and functioning of mediosphere and then discusses it in the context of ethics. It is a phenomenon which belongs to the domain of environment, and therefore exhibits a high level of effectiveness. Mediosphere is an environment generated by the media which are used by people. The human being is the most important element of this environment and influences it in a peculiar way. Hence, each mediosphere is different. The structure and functioning of mediosphere is affected by its layers, namely logosphere, iconosphere, sonosphere, and galenosphere. A consequence of the ‘environmental’ nature of mediosphere is that negative effects of particular phenomena pertaining to the activity of the media are cumulated. Therefore, the ethical aspects of mediosphere are very important and topical. Reflections on this facet of mediosphere may prove useful for both people involved in the media and teachers, whose task, among others, is to prepare students for an adequate reception of what is offered by the press, radio, television, and the Internet. The discussion includes reference to examples of studies by those Western authors who propose practical guidelines and precautionary measures to prevent violation of ethical principles in the functioning of mediosphere.